Chracterization of Solvent-Extractable Hydrocarbons in Airborne and Roadside Soil Particles of Kuala Lumpur, Malaysia - Yousef M.J. Omar, Nasr; bin Abas, M. Radzi; Aziz Ketuly, Kamal; Mohd. Tahir, Norhayati (Malaysian Journal of Science, 2002)
Solvent-extractable hydrocarbons were isolated from PM_10 airborne particles and roadside soil particles collected during the period from November 1998 to January 1999 from the city centre and the suburb of Kuala Lumpur, Malaysia. Hydrocarbons identified were n-alkanes, polycyclic aromatic hydrocarbons (PAHs), and petroleum molecular markers including pristane, phytane, hopanes, and steranes. Molecular distributions of these compounds as well as geochemical diagnostic ratios were determined in order to identify the sources of hydrocarbons. Samples of lubricating oils were also analyzed for comparisons. The major source of hydrocarbons was petrogenic emissions with some contribution from biogenic sources such as waxes of higher plants